2010
DOI: 10.1590/s0103-73312010000100007
|View full text |Cite
|
Sign up to set email alerts
|

Um enfoque sanitário sobre a demanda judicial de medicamentos

Abstract: No Brasil, apesar dos avanços da assistência farmacêutica, permanecem falhas na garantia do acesso dos cidadãos aos medicamentos pelo Estado. Nos últimos anos, vem crescendo a reivindicação de medicamentos por parte do cidadão via sistema judiciário. Os objetos dessas solicitações são tanto os medicamentos em falta na rede pública como aqueles ainda não incorporados pelo Sistema Único de Saúde. Este fenômeno pode ser analisado sob diferentes perspectivas, inclusive a sanitária, entendida aqui como os desfechos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
0
6
0
6
Order By: Relevance
“…Many of these legal cases seek to ensure the right of access for patients to expensive medicines that are not always available on SUS and many times without any proven benefits or in some cases are considered deleterious 1,2 . This situation has led to the approval of Law n° 12401 in April 2011 which aimed to regulate the concept of integrality and make therapeutic assistance more readily available.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these legal cases seek to ensure the right of access for patients to expensive medicines that are not always available on SUS and many times without any proven benefits or in some cases are considered deleterious 1,2 . This situation has led to the approval of Law n° 12401 in April 2011 which aimed to regulate the concept of integrality and make therapeutic assistance more readily available.…”
Section: Introductionmentioning
confidence: 99%
“…With effect, several studies have shown that medical prescriptions are accepted as sufficient proof by the courts (incontestable and legitimate) of the need for use in relation to innumerable medications 12,[22][23][24] . Certainly, the prescription and the medical reports are and should be fundamental elements for allowing the courts to take their decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Uma das formas utilizadas para divulgação dos novos medicamentos à classe médica, estimulando o uso de medicamentos em indicações não aprovadas no registro, tem sido o financiamento da educação continuada dos prescritores 24 . Diante desse cenário de crescentes desafios e interesses diversos, a informação fidedigna e independente do setor produtivo é uma ferramenta imprescindível para a prescrição racional de medicamentos e para a proteção da saúde dos cidadãos.…”
Section: Discussionunclassified